Comparative analysis of IoT based products, technology and integration of IoT with cloud computing. Issue 2 (1st March 2020) - Sharma, Bhisham; Obaidat, Mohammad S.
Abstract : The advanced technology Internet of Things (IoT), a recent development in wireless sensor networks, provides a way to connect surrounding physical objects to the Internet in a dynamic way. There is an advantage of using IoT technology protocols as it requires less network bandwidth, minimum code space and hence reduces access time. Major IoT provider companies have several IoT products in the gadget market to make consumers' life effortlessly easy. Several research gaps regarding the scalability of IoT with other platforms have been identified by reviewing the existing literature and also explained essential information about the integration of IoT with cloud computing. Major technology big giants Apple, Google, and Amazon's products are differentiated on the basis of measurement parameters such as their prices, streaming options, customisable appearance methods, major partnership companies related information appearing. A prototype of Apple's Home Kit and Samsung SmartThings is developed to show the characteristics of smart home products for the user, which helps in better decision making of IoT platform providers.